Mobilitätskosten 2030: Autofahren und ÖPNV-Nutzung werden teurer. Ein vergleichende Abschätzung MIV vs. ÖPNV. - Hunsicker, Frank; Sommer, Carsten (Deutscher Verkehrs-Verl., 2009)
Trotz der aktuellen Baisse der Kraftstoffpreise und trotz des derzeitigen Medienrummels um Elektrofahrzeuge werden die Kosten für Autofahrer auf lange Sicht überproportional zunehmen. Dazu wird neben den absehbar wieder ansteigenden Preisen für Rohöl nicht zuletzt die noch als Tabuthema geltende Pkw-Maut beitragen. Die Mobilitätskosten des öffentlichen Verkehrs auf Schiene und Straße könnten vergleichsweise moderat steigen, sofern öffentliche Mittel wie bisher erhalten bleiben und weitere Rationalisierungspotenziale voll ausgeschöpft werden können.

As part of a long term research project that involved forecasting traffic demand up to 2030, a comprehensive analysis was made to ascertain alternative scenarios for mobility cost increases in the case of private cars and public transport. Accordingly, costs for private car users are expected to go up by some 60 % within a span of 25 years due to ongoing petrol price increases and the anticipated introduction of user charges, in the medium term, for the federal road system. Public transport users will also have to face higher mobility costs although, with regard to the calculated target values, the range of variable factors is known to be much greater. Dependence on political decisions, on the level of public sector joint financing arrangements, and on the extent of transport carriers, productivity enhancement, is deemed to be too excessive. At best, public transport ticket prices will increase less than the cost of using private cars, yet different scenarios may still emerge. The economic crisis will obviously lead to a further scaling down of the state's financial expenditure. Finally, a review is offered of hybrid- and electro-based mobility. On a long term basis, however, this type of technology does not - as specially noted - signify a more advantageous cost alternative to combustion engines.
Mobility costs by 2030: using private cars and public transport will become more expensive.
Keywords: Verkehr; Verkehrspreis; Modellrechnung; Kostenvergleich; ÖPNV; Individualverkehr; Autoverkehr; Kostenschätzung; Verkehrsprognose; Verkehrspreis; Kostenentwicklung